Salivary gland degeneration and vitellogenesis in the ixodid tick Amblyomma hebraeum: surpassing a critical weight is the prerequisite and detachment from the host is the trigger - Friesen, Kevin (My University, 2009)
The normal engorged body weight of female ixodid ticks (Acari: Ixodidae) is about 100× the unfed weight. Virgin female Amblyomma hebraeum normally do not feed beyond 10× the unfed weight. However, about 10–20% of a population of virgins will feed to perhaps 20× the unfed weight, but not much beyond that. In A. hebraeum, when females surpass about 10× the unfed weight, the following changes in physiology occur if they are removed from the host: (a) they will not reattach if given the opportunity, (b) their salivary glands (SGs) will undergo autolysis within 4 days if they are mated or 8 days if they are virgin, and (c) egg maturation and oviposition will occur in due course. Mated or virgin female ticks removed from the host below about 10× the unfed weight do not experience the latter changes (Kaufman, W.R., Lomas, L., 1996. ‘Male Factors’ in ticks: their role in feeding and egg development. Invertebrate Reproduction and Development 30, 191–198). In 1984 we named this transitional weight, the ‘critical weight’ (CW). Its absolute value is probably a species-specific characteristic (Kaufman, W.R., 2007. Gluttony and sex in female ixodid ticks: how do they compare to other blood-sucking arthropods? Journal of Insect Physiology 53, 264–273). Although mated females tend to engorge within a day of surpassing the CW, virgin females surpassing the CW can remain attached to the host for at least several weeks more. It is not known whether the physiological changes in the SGs and ovaries listed above occur in those large virgins that remain attached, although we suppose that this would be maladaptive. Instead, we hypothesize in this study that surpassing the CW is only a prerequisite for inducing these changes, and that detachment is the actual trigger. We support our hypothesis by demonstrating that large virgins, remaining attached to a host for 8 days, did not undergo SG degeneration nor complete egg maturation during the attachment period. Those changes occurred only within 8 days following detachment. So some type of sensory information associated with attachment to the host, and still undefined, inhibits expression of the physiological changes hitherto associated merely with surpassing the CW.
Keywords: ixodid ticks; amblyomma hebraeum; ecdysteroids; vitellogenesis; ovarian development; critical weight; tick salivary glands